Long-term analysis of the physical and technical performance of players in Russian Premier Liga football matches from 2015 to 2022 - Dzhilkibaeva, N.; Khomiakova, A.; Kalinin, E.; Kuzmichev, V.; Lunina, A. (Journal of Physical Education and Sport, 2024)
Problem statement: While extensive research exists on the physical and technical performance of players in the world's top football leagues, there is a considerable lack of comprehensive studies on professional players from lower-ranking leagues. Conducting new research on performance in these less-studied leagues across various countries will not only help determine their relative performance levels but also allow us to assess the evolution of global football.